Design and Usability Evaluation of Chronic Obstructive Pulmonary Disease Self-Care Application Based on Android - Marjan Ghazi Saeedi; Mohammad Amin Abbasi Eslamloo; Kobra Darabiyan; Elham Ataei (Tehran University of Medical Sciences, 2023)
Background and Aim: Despite the continuous progress in medicine, COPD (Chronic Obstructive Pulmonary Disease) is still a progressive, incurable and chronic respiratory condition that limits the patients' functions in various dimensions, and significantly reduce their quality of life. In this way, self-care of patients and the use of related tools have a significant effect in disease control and treatment. The purpose of this research was design and development of an android-based application for COPD. Materials and Methods: This research was a descriptive developmental type with a practical approach. Initially, based on the study of library resources, guidelines, and the examination of the medical records of COPD inpatients in Firouzabadi Hospital, a questionnaire was designed to identify the information requirements, data items and features of the application. Then it was reviewed and finalized by a sample of 10 (randomized and convenience sampling) internal and lung specialist doctors in Firouzabadi and Hazrat Rasool hospitals affiliated to Iran University of Medical Sciences. The data was analyzed using descriptive statistics, and then scenario tables and UML diagrams were illustrated to show the overall flow of the application. The application was designed and developed using the Java programming language in the Android Studio 2021 platform. After installing the application on the mobile phones of ten COPD patients of the internal and pulmonary clinic of Firouzabadi Shahre Rey Hospital, and using it for a week, the opinions of the patients about the usability of the application were collected through the QUIS questionnaire, and analyzed.  Results: Application sections were determined following experts' survey, personal information items, clinical information, disease management, reporting, and training points, which were provided to patients after design for use and evaluation. At the end of the research, the results of the evaluation of the usability and satisfaction level of the application showed that from the patients' point of view, the application is at a good level with an average score of 1.8 (out of 10 points). Conclusion: The developed self-care application can be used to increase awareness, help to manage the disease, increase the level of quality of life, and reduce the complications and disease burden for patients with COPD.